Aims to Increase Student Participation in Class IX Through a Problem Based Learning Model (PBL) Assisted by Game Media on Civics Lessons at SMPN 21 Mataram - diyat, baiq radya; Sumardi, Lalu; Kurniawansyah, Edy; Ismail, M (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2025)
This study aims to increase student learning participation by applying the PBL model assisted by Game Media. The type of research used in this study is Classroom Action Research (PTK) model Kemmis and Mc Tanggart. There are four stages of this class action research, namely 1) planning 2) Implementation 3) Observation 4) Reflection. The subjects of this research were all students of class IX-B as many as 17 students at SMPN 21 Mataram in the 2024/2025 academic year. Data collection techniques are observation and interview. The instruments used in this study were student learning participation observation sheets and teacher learning implementation observation sheets. Data analysis in this study used quantitative and qualitative data analysis. Quantitative data analysis is used to analyze quantitative data while qualitative data analysis is used to analyze qualitative data. The results of preliminary observations that student learning participation will increase by using the Problem Based Learning learning model assisted by Game Media. Student learning participation obtained in Cycle I has reached the completeness of four indicators out of six indicators of student learning participation. As for the second cycle, the completeness of student learning participation has increased significantly, namely reaching the completeness of all indicators of student learning participation. Therefore, this research can be considered successful because it has met the criteria for the completeness of student learning participation from cycle I to cycle II. Students' learning participation is better, after applying the Problem Based Learning model assisted by Game Media.